Prevalence, Genetic Heterogeneity, and Antibiotic Resistance Profile of Listeria spp. and Listeria monocytogenes at Farm Level : A Highlight of ERIC- and BOX-PCR to Reveal Genetic Diversity - Lesley, Maurice Bilung; Lai, Sin Chai; Ahmad Syatir, Tahar; Chong, Kian Ted; Kasing, Apun (Hindawi Publishing, 2018)
This study aimed to identify Listeria spp. and L. monocytogenes, characterize the isolates, and determine the antibiotic resistance profiles of the isolates Listeria spp. and L. monocytogenes in fresh produce, fertilizer, and environmental samples from vegetable farms (organic and conventional farms). A total of 386 samples (vegetables, soil, water, and fertilizer with manure) were examined. The identification of bacterial isolates was performed using PCR and characterized using ERIC-PCR and BOX-PCR. The discriminating power of the typing method was analyzed using Simpson’s Index of Diversity. Thirty-four (n=34) Listeria isolates were subjected to antimicrobial susceptibility test using the disc-diffusion technique. The PCR analysis revealed that Listeria spp. were present in 7.51% (29/386) of all the samples (vegetable, soil, fertilizer, and water). None of the samples examined were positive for the presence of L. monocytogenes. Percentages of 100% (15/15) and 73.30% (11/15) of the Listeria spp. isolated from vegetables, fertilizer, and soil from organic farm B had indistinguishable DNA fingerprints by using ERIC-PCR and BOX-PCR, respectively. Listeria spp. isolated from 86 samples of vegetable, fertilizer, and environment of organic farm A and conventional farm C had distinct DNA fingerprints. Simpson’s Index of Diversity, D, of ERIC-PCR and BOX-PCR is 0.604 and 0.888, respectively. Antibiotic susceptibility test revealed that most of the Listeria spp. in this study were found to be resistant to ampicillin, rifampin, penicillin G, tetracycline, clindamycin, cephalothin, and ceftriaxone. The isolates had MAR index ranging between 0.31 and 0.85. In conclusion, hygienic measures at farm level are crucial to the reduction of Listeria transmission along the food chain.